2019
DOI: 10.1515/hmbci-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soy on scopolamine-induced spatial learning and memory impairments are comparable to the effects of estradiol

Abstract: Background Modulatory effects of soy extract and estradiol on the central nervous system (CNS) have been reported. The effect of soy on scopolamine-induced spatial learning and memory in comparison to the effect of estradiol was investigated. Materials and methods Ovariectomized rats were divided into the following groups: (1) control, (2) scopolamine (Sco), (3) scopolamine-soy 20 (Sco-S 20), (4) scopolamine-soy 60 (Sco-S 60), (5) scopolamine-estradiol 20 (Sco-E 20) and (6) scopolamine-estradiol 60 (Sco-E 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…Consistent with our ndings, some previous investigations have also reported the cognition-impairing effects of scopolamine using behavioral tests (Marefati et al 2019;Brinza et al 2021). Accordingly, Hoang showed that the mean latencies and swimming distances increased by the administration of scopolamine (Hoang et al 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our ndings, some previous investigations have also reported the cognition-impairing effects of scopolamine using behavioral tests (Marefati et al 2019;Brinza et al 2021). Accordingly, Hoang showed that the mean latencies and swimming distances increased by the administration of scopolamine (Hoang et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Our data revealed that scopolamine-induced memory loss was accompanied with increase in AChE activity and oxidative stress in the brain tissue. These results are in line with those of the previous studies (Marefati et al 2019;Brinza et al 2021;Boiangiu et al 2020). In this regard, Brinza et al (2021) reported a signi cant reduction in the total antioxidant content along with the increased AChE activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The retention of memory was examined 24 hours after acquisition trials by using a probe trial in which the platform was removed and the tested rat was allowed to explore the pool. Swimming tracks were recorded in all trials using a camera above the centre of the maze and video‐tracking software (Borj Sanat Azma) 52,53 …”
Section: Methodsmentioning
confidence: 99%
“…Swimming tracks were recorded in all trials using a camera above the centre of the maze and video-tracking software (Borj Sanat Azma). 52,53 The reversal stage started the day after the retention trial. During In all analyses, the interaction term was removed if not significant and P-values for the main effects were then given.…”
Section: Conditioned Place Preferencementioning
confidence: 99%